Unilateral Resection of the Anterior Medial Temporal Lobe Impairs Odor Identification and Valence Perception - Juran, Stephanie A.; Lundström, Johan N.; Geigant, Michael; Kumlien, Eva; Fredrikson, Mats; Åhs, Fredrik; Olsson, Mats J. (Frontiers in Psychology, 2016)
The anterior medial temporal lobe (TL), including the amygdala, has been implicated in olfactory processing, e.g. coding for intensity and valence, and seems also involved in memory. With this background, the present study evaluated whether anterior medial TL-resections in temporal lobe epilepsy affected intensity and valence ratings, as well as free and cued identification of odors. These aspects of odor perception were assessed in thirty-one patients with unilateral anterior medial TL-resections (17 left, 14 right) and 16 healthy controls. Results suggest that the anterior medial TL is in particular necessary for free, but also cued, odor identification. TL resection was also found to impair odor valence, but not intensity ratings. Left resected patients rated nominally pleasant and unpleasant as more neutral suggesting a special role for the left anterior temporal lobe in coding for emotional saliency in response to odors.